2013
DOI: 10.1038/srep02448
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Patterns of Dislocations at Nodes in (111) Semi-coherent FCC Interfaces

Abstract: In semi-coherent interface, a superposed network of interface dislocations accommodates the attendant coherency strains in the adjacent crystals and their intersections (referred to as nodes) can act as sinks and sources for point defects because of the low formation energy. Nodes in {111} semi-coherent interfaces are characterized with a spiral pattern (SP), wherein the line direction of each dislocation entering a node curves. The structure of SP nodes is able to switch between condensed and expanded by eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 37 publications
(45 reference statements)
6
51
0
Order By: Relevance
“…Dynamic boundary conditions were adopted to achieve zero normal stress and zero shear stresses in the interface plane. We found that a node can adopt different atomic structures corresponding to mechanical perturbation, thermal fluctuation, or vacancy/interstitial absorption at a node [31][32][33]37,38,[47][48][49]. The details of the different node structures and dislocations nucleation are discussed in later sections.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Dynamic boundary conditions were adopted to achieve zero normal stress and zero shear stresses in the interface plane. We found that a node can adopt different atomic structures corresponding to mechanical perturbation, thermal fluctuation, or vacancy/interstitial absorption at a node [31][32][33]37,38,[47][48][49]. The details of the different node structures and dislocations nucleation are discussed in later sections.…”
Section: Methodsmentioning
confidence: 96%
“…These have been shown to produce reliable results [37,38,[42][43][44]. A Cu-Ni bi-crystal model containing a single Cu-Ni interface is assembled by joining two semi-infinite Cu and Ni crystals with the same crystallographic orientations and coordinates, x along ½11 2, y along ½111, and z along½1…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, there are cases where the interface dislocations lose the privilege to nucleate lattice dislocations. For instance, the core-size of the misfit dislocation in the interfaces with lower shear resistance (such as the FCC {111} interfaces) tends to spread, thereby reducing the strain concentration associated with the dislocation core necessary for the nucleation [20][21][22]32]. In this scenario, the dislocation intersections (nodes) may be the only source available for lattice dislocation nucleation.…”
Section: Introductionmentioning
confidence: 99%